2015
DOI: 10.1007/s10900-014-9985-9
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Smoking Cessation Related to a Smoke-Free Policy Among Homeless Adults

Maya Vijayaraghavan,
John P. Pierce

Abstract: Homeless adults have among the highest rates of cigarette smoking. Few studies have explored the potential of smoke-free policies as facilitators of smoking cessation or harm reduction among sheltered homeless adults. We focused on clients of a homeless shelter in San Diego, California. The facility prohibited smoking indoors and outdoors within five blocks of the building, and permitted smoking during four smoking breaks during the day in designated smoking zones away from the building. Current and former smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…Shelters have smoke-free policies that may motivate individuals to make quit attempts. 2,42 Few shelters offer on-site resources, but most provide referrals to community-based resources for smoking cessation. 43 These factors may also encourage quit attempts among homeless clients.…”
Section: Discussionmentioning
confidence: 99%
“…Shelters have smoke-free policies that may motivate individuals to make quit attempts. 2,42 Few shelters offer on-site resources, but most provide referrals to community-based resources for smoking cessation. 43 These factors may also encourage quit attempts among homeless clients.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey of homeless shelters in San Diego County showed that all facilities had an indoor ban on smoking, 61.5% had an outdoor designated smoking zone and 25% had a campus-wide ban on smoking 88. In two cross-sectional studies of sheltered homeless adults, the majority of participants were supportive of indoor smoke-free policies 89 90. In a shelter that had an indoor and outdoor smoking ban, most homeless adults reported reductions in consumption, and about half reported either having made a quit attempt or getting ready to quit completely 90…”
Section: Clean Indoor Air Lawsmentioning
confidence: 99%
“…There is research supporting the enactment of clean indoor air policies in homeless housing programs; pilot studies suggest that such policies lead to reduced smoking rates and reduced carbon monoxide exposure (Businelle et al, 2015; Vijayaraghavan & Pierce, 2015). Providing on-site smoking cessation therapy in transitional housing has led to increased abstinence and reduced carbon monoxide exposure (Goldade et al, 2011; Okuyemi, Thomas, et al, 2006; Power, Mallat, Bonevski, & Nielssen, 2015; Segan, Maddox, & Borland, 2015; Shelley, Cantrell, Wong, & Warn, 2010).…”
Section: Introductionmentioning
confidence: 99%